Forced displacement: A rapidly rising vulnerability and its challenges for an inclusive and sustainable Asia and the Pacific - Tulsi Charan Bisht (Asian Development Bank Institute (ADBI), 2024)
Forced displacement results from some form of direct or indirect violence or factors known as push factors. Such migration is not an outcome of volition but of coercion. Based on a systematic review of relevant literature, this report presents rapidly rising trends of forced displacement in the Asia and Pacific region. Three main causes of forced displacement are outlined and discussed-violence, inequality and environment and climate change. Following a political economy analysis, the report stresses the intersectionality of the three factors that ultimately results in forced displacement. The report highlights systemic inequality as the root cause for forced displacement and concludes that force displacement, if remains unchecked, could pose challenges to achieve the goals of inclusive and sustainable development as well as achieving the Sustainable Development Goals by 2030 in the region. The report recommends recognizing forced displacement as an emergent vulnerability that would require a coordinated humanitarian and developmental approach to tackle its rapid rise.
Keywords: O19; 330; forced displacement; forced migration; refugees; asylum seekers; internally displaced persons; stateless persons; environmental refugees; climate change-induced displacement; reverse migration; forced migration theories